Tribological improvement of a high-speed train brake system and friction-induced vibration energy harvesting via a sandwich damping piezoelectric structure. (December 2022) - Xiang, Z.Y.; Zheng, P.W.; He, D.Q.; Mo, J.L.; Zhu, S.; Gou, Q.B.; Du, L.Q.
Abstract: A sandwich damping piezoelectric structure (SDPS) was designed to improve the wear and friction, reduce the friction-induced vibration and noise (FIVN) of high-speed train brake system, and convert friction-induced vibration (FIV) energy into electrical energy. Tribological tests were carried out to investigate the effect of the SDPS on the tribological behavior and the conversion efficiency of FIV energy into electrical energy. The results show that the proposed SDPS can convert FIV energy into electrical energy due to deformation, and the perforated structure produces greater deformation and a higher output voltage. The SDPS installed in the braking system improves the contact and wear behavior of the friction block, which reduces the FIV intensity, and can transform FIV energy into electrical energy.